Methods to use when teaching legal ethics in South Africa - Deventer, E Snyman-Van (Obiter, 2021)
SUMMARY Teaching legal ethics must be more than just compliance with the requirements of the legal profession but also an opportunity for every law faculty or law school to make a contribution to the development of a culture of ethics. Whether legal ethics are taught in a stand-alone module or integrated in any other module, the lecturer has to determine the goals and objectives of the module and how to achieve them and also how to assess whether the set goals and objectives have been achieved. In designing a module on legal ethics, the lecturer’s own style and personality will influence the module’s structure, style and technique. The lecturer therefore needs to choose the teaching method that suits him or her. Teaching methods identified include case studies, problems, Socratic instruction, discussions, group discussions, video and film presentations, co-curricular activities, lectures, the use of social media and the Internet, clinical participation, role play and simulations, law clinics, written assignments, one-minute essays, games, and moot courts. Most of these methods are not exclusive; in teaching, one most often uses a combination of the different methodologies. This article focuses mainly on the methods to be used (the “how” question) when teaching legal ethics. The objectives (the “what and why” questions) and structural aspects (the “where” questions) are also dealt with briefly. The “how” question is important because how we approach teaching needs to reflect the changing student body, the increase in student numbers and the changing learning style of our students. In answering the “how” question, various methodologies are discussed as possible ways to teach legal ethics in a South African context.